Sosialisasi UU ITE, Ditengah Maraknya Penggunaan Sosial Media - Moh. Yusuf DM; Roki Hardianto (Journal of Community Engagement Research for Sustainability, 2022)
Community service activities were carried out for community groups in RT 03 RW 08 Umban Sari Village, Rumbai District, Pekanbaru City. This needs to be socialized because the ITE Law has taken many victims, especially the lower class people who do not understand the implementation of the ITE Law. In addition, because social media has been used by the average community, not only young people but parents have become important things. To avoid the misuse and application of the ITE Law, it is necessary to provide assistance and socialization to the community. This activity was chaired by Dr. Mohd. Yusuf DM, M.H, Ph.D has competence in the field of Criminal Law from the Faculty of Law and consists of Roki Hardianto, M.Kom competence in Information Technology from the Faculty of Computer Science. The planned outputs are scientific articles published in national journals and teaching modules from this activity.